PENGARUH KADAR CALCIUM SULFOALUMINATE SEBAGAI SUBSTITUSI SEMEN TERHADAP PROPERTI SEGAR, MENGERAS, DAN DURABILITAS MORTAR - Yudhi Noer Cahya Wijayadi; Herry Suryadi Djayaprabha (Jurnal Teknik Sipil, 2023)
Due to the apprehension about global warming caused by extensive carbon dioxide (CO2) emissions, the construction industry is striving to develop alternate composite cement. Calcium sulfoaluminate (CSA) cement has been utilized since it consumes less energy and discharges less CO2 during production in comparison to Ordinary Portland Cement (OPC). CSA cement has gained popularity due to its exceptional abilities like rapid setting, high strength, and durability. In construction materials, CSA has been extensively used as a substitute binder, either partially or entirely replacing OPC. This research involved the partial substitute of OPC with CSA in varying amounts of 0%, 12.5%, 25%, 37.5%, and 50% while maintaining a fixed water-to-binder ratio of 0.4 for mortar production. The study aimed to explore the fresh properties, hardened properties, and durability of mortar. The results indicated that the optimal CSA proportion of 12.5% exhibited in compressive strength of 36.70 MPa and flexural strength of 7.36 MPa at 28 days. Furthermore, the results revealed that the CSA proportion of 12.5% displayed satisfactory durability-related properties at 28 days with a drying shrinkage value of 640 mm/m, ultrasonic pulse velocity of 4274 m/s, and a sorptivity coefficient of 5.46×10-4 mm/s1/2.